Improved HCN channels in pyramidal neurons and their new expression levels in pericytes and astrocytes in the gerbil hippocampal CA1 subfield following transient ischemia - Park, Joon Ha (Int J Mol Med, 2019)
Hyperpolarization-activated cyclic nucleotide-gated (HCN) channels have been known to participate in the regulation of neuronal excitability, synaptic transmission and long-term potentiation in the hippocampus. The present study investigated transient ischemia-induced changes of HCN1 and HCN2 expressions in the Cornu Ammonis 1 (CA1) subfield of the hippocampus in gerbils subjected to 5 min transient global cerebral ischemia (tgCI). Neuronal death was exhibited in pyramidal neurons of the striatum pyramidale in the CA1 subfield 4 days after tgCI. HCN1 and HCN2 immunoreactivities were demonstrated in intact CA1 pyramidal neurons, and were transiently and markedly increased in the CA pyramidal neurons at 6 h after ischemia. Thereafter, they gradually decreased in a time-dependent manner. A total of 4 days after ischemia, HCN1 and HCN2 immunoreactivities were barely detected in the CA1 pyramidal neurons; however, HCN1 and HCN2 were began to be expressed in pericytes and astrocytes at 4 days after ischemia. The results indicated that HCN1 and HCN2 expression levels were apparently changed in the gerbil hippocampal CA1 subfield following tgCI and suggested that ischemia-induced alterations in HCN1 and HCN2 expression levels may be closely associated with the death of CA1 pyramidal neurons following 5 min of tgCI.